The success principles : how to get from where you are to where you want to be - Canfield, Jack, 1944-; Switzer, Janet, 1953- (New York William Morrow, an imprint of Harper Collins Publishers, 2005)
Since its publication a decade ago, Jack Canfield's practical and inspiring guide has helped thousands of people transform themselves for success. Now, he has revised and updated his essential guidebook to reflect our changing times. The Success Principles will teach you how to increase your confidence, tackle daily challenges, live with passion and purpose, and realize all your ambitions. Filled with memorable and inspiring stories of CEO's, world-class athletes, celebrities, and everyday people, it spells out the 67 timeless principles used by successful men and women throughout history--proven principles and strategies that can be adapted for your own life, whether you want to be the best salesperson in your company, become a leading architect, score top grades in school, lose weight, buy your dream home, make millions, or just get back in the job market. Taken together and practiced every day, these principles will change your life beyond your wildest dreams.--Publisher's description
The fundamentals of success -- Transform yourself for success -- Build your success team -- Create successful relationships -- Success and money -- Success in the digital age
"Fully revised and updated"--Cover
First edition published: New York : Harper Resource Book, 2005
Includes bibliographical references and index
Keywords: Success -- Psychological aspects